Histopathological findings related to protozoan Perkinsus infection in Manila clams (Ruditapes philippinarum) - L. Mandrioli; M. Anjomanibenisi; B. Bacci; B. Brunetti (Journal of Comparative Pathology, 2025)

Multiplex immunohistochemistry and supervised machine learning for immune cells topography in canine PDL1 tested urothelial Carcinoma - L. Muscatello; T. Franceschini; C. Tugnoli; A. Grillini; B. Bacci; G. Avallone; P. Valenti; M. Fiorentino; G. Sarli (Journal of Comparative Pathology, 2025)

ELIME-IMS hybrid assay for Salmonella detection in swine mesenteric lymph nodes at slaughterhouse - M. Trevisani; M. Conter; M. Cecchini; L. Lamperti; L. Andriani; M. Rega; C. Bacci; M. Perri; S. Bonardi (Food Microbiology, 2025)

Detection of carbapenemase- and ESBL-producing Klebsiella pneumoniae from bovine bulk milk and comparison with clinical human isolates in Italy - S. Bonardi; C.S. Cabassi; E. Fiaccadori; S. Cavirani; A. Parisi; C. Bacci; L. Lamperti; M. Rega; M. Conter; F. Marra; C. Crippa; L. Gambi; et al. (International Journal of Food Microbiology, 2023)

Acute Toxicity and Sub-lethal Effects of the Essential Oil of Aristolochia trilobata and Its Major Constituents on Nasutitermes corniger (Termitidae: Nasutitermitinae) - A A Santos; C R Melo; B M S Oliveira; A S Santana; A C C Santos; T S Sampaio; A F Blank; P F Cristaldo; A P A Araújo; L Bacci (Neotropical Entomology, 2019)

Lethal Effect and Behavioral Responses of Leaf-Cutting Ants to Essential Oil of Pogostemon cablin (Lamiaceae) and Its Nanoformulation - A G Rocha; B M S Oliveira; C R Melo; T S Sampaio; A F Blank; A D Lima; R S Nunes; A P A Araújo; P F Cristaldo; L Bacci (Neotropical Entomology, 2018)

Phylogenetic patterns of ant–fungus associations indicate that farming strategies, not only a superior fungal cultivar, explain the ecological success of leafcutter ants - Ulrich G. Mueller; Melissa R. Kardish; Heather D. Ishak; April M. Wright; Scott E. Solomon; Sofia M. Bruschi; Alexis L. Carlson; Maurício Bacci (Molecular Ecology, 2018)
To elucidate fungicultural specializations contributing to ecological dominance of leafcutter ants, we estimate the phylogeny of fungi cultivated by fungus‐growing (attine) ants, including fungal cultivars from (i) the entire leafcutter range from southern South America to southern North America, (ii) all higher‐attine ant lineages (leafcutting genera Atta , Acromyrmex ; nonleafcutting genera Trachymyrmex , Sericomyrmex ) and (iii) all lower‐attine lineages. Higher‐attine fungi form two clades, Clade‐A fungi ( Leucocoprinus gongylophorus , formerly Attamyces ) previously thought to be cultivated only by leafcutter ants, and a sister clade, Clade‐B fungi, previously thought to be cultivated only by Trachymyrmex and Sericomyrmex ants. Contradicting this traditional view, we find that (i) leafcutter ants are not specialized to cultivate only Clade‐A fungi because some leafcutter species ranging across South America cultivate Clade‐B fungi; (ii) Trachymyrmex ants are not specialized to cultivate only Clade‐B fungi because some Trachymyrmex species cultivate Clade‐A fungi and other Trachymyrmex species cultivate fungi known so far only from lower‐attine ants; (iii) in some locations, single higher‐attine ant species or closely related cryptic species cultivate both Clade‐A and Clade‐B fungi; and (iv) ant–fungus co‐evolution among higher‐attine mutualisms is therefore less specialized than previously thought. Sympatric leafcutter ants can be ecologically dominant when cultivating either Clade‐A or Clade‐B fungi, sustaining with either cultivar‐type huge nests that command large foraging territories; conversely, sympatric Trachymyrmex ants cultivating either Clade‐A or Clade‐B fungi can be locally abundant without achieving the ecological dominance of leafcutter ants. Ecological dominance of leafcutter ants therefore does not depend primarily on specialized fungiculture of L. gongylophorus (Clade‐A), but must derive from ant–fungus synergisms and unique ant adaptations.

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Relative abundance of heat shock proteins and clusterin transcripts in spermatozoa collected from boar routinely utilised in an artificial insemination centre: preliminary results - A. Zannoni; C. Bernardini; A. Zaniboni; E. Ferlizza; D. Ventrella; M. L. Bacci; M. Forni (Veterinary Research Communications, 2017)

Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - J. Sosa-Calvo; A. Ješovnik; C. T. Lopes; A. Rodrigues; C. Rabeling; M. Bacci; H. L. Vasconcelos; T. R. Schultz (Insectes Sociaux, 2017)

Life table determination of thermal requirements of the tomato borer Tuta absoluta - J. C. Martins; M. C. Picanço; L. Bacci; R. N. C. Guedes; P. A. Santana; D. O. Ferreira; M. Chediak (Journal of Pest Science, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Long-term efficacy of microbiology-driven periodontal laser-assisted therapy - F. S. Martelli; E. Fanti; C. Rosati; M. Martelli; G. Bacci; M. L. Martelli; E. Medico (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Pulmonary kinetic expression of the endothelin system in a swine model of endotoxic shock - A. Zannoni; C. Bernardini; F. Gentilini; M. Giunti; M. L. Bacci; M. Forni (Veterinary Research Communications, 2010)

Molecular phylogeny and karyotype differentiation in Paratelmatobius and Scythrophrys (Anura, Leptodactylidae) - L. B. Lourenço; M. Bacci-Júnior; V. G. Martins; S. M. Recco-Pimentel; C. F. B. Haddad (Genetica, 2008)

Matrix Metalloproteinases -2 and -9 in Swine Luteal Tissue Angiogenesis and Angioregression - L. A. Ribeiro; M. E. Turba; C. Bernardini; A. Zannoni; M. L. Bacci; M. Forni (Veterinary Research Communications, 2007)

Detection and Characterization of Yersinia enterocolitica from Pigs and Cattle - S. Bonardi; A. Paris; C. Bacci; M. D’Incau; L. Ferroni; F. Brindani (Veterinary Research Communications, 2007)

A Brief Overview of Transgenic Farm Animals - M. L. Bacci (Veterinary Research Communications, 2007)

Differential Expression of VEGF Isoforms in Pig Corpora Lutea Throughout the Estrous Cycle - L. A. Ribeiro; A. Zannoni; M. L. Bacci; M. Forni (Veterinary Research Communications, 2006)

Variability of non-mutualistic filamentous fungi associated withAtta sexdens rubropilosa nests - A. Rodrigues; F. C. Pagnocca; M. Bacci; M. J. A. Hebling; O. C. Bueno; L. H. Pfenning (Folia Microbiologica, 2005)

Nesting biology of the fungus growing ants Mycetarotes Emery (Attini, Formicidae) - S. E. Solomon; U. G. Mueller; T. R. Schultz; C. R. Currie; S. L. Price; A. C. Oliveira da Silva-Pinhati; M. Bacci; H. L. Vasconcelos (Insectes Sociaux, 2004)